1976
DOI: 10.1007/bf01181655
|View full text |Cite
|
Sign up to set email alerts
|

The ultrastructure of Auerbach's plexus in the guinea-pig. I. Neuronal elements

Abstract: The ultrastructural features of nerve cell bodies and axon profiles within Auerbach's plexus in the stomach, ileum, caecum and colon of the guinea-pig have been examined. Nerve cell bodies have been tentatively classified into nine different types according to their size, distribution of organelles, location and relationship to satellite cells. Except for cell size, no attempt has been made to correlate ultrastructual with light microscopical observations. On the basis of vesicular size, shape and content, eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
5

Year Published

1981
1981
2009
2009

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(45 citation statements)
references
References 34 publications
0
40
0
5
Order By: Relevance
“…There are more than a dozen established or putative neurotransmitters (Furness and Costa, 1982b), and electron microscopy has been used to identify at least eight different neuronal classes (Cook and Burnstock, 1976). Extracellular recording has led to the description of six patterns of neuronal activity (Wood, 1981).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are more than a dozen established or putative neurotransmitters (Furness and Costa, 1982b), and electron microscopy has been used to identify at least eight different neuronal classes (Cook and Burnstock, 1976). Extracellular recording has led to the description of six patterns of neuronal activity (Wood, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Radioautography The dense HRP reaction product tended to obscure these specializations, and they are rare and rudimentary, in any case, in the ENS (Baumgarten et al, 1970;Cook and Burnstock, 1976;Manber and Gershon, 1979) (current reccrd on lower trace) induces action potentials followed by an AH. Current pulses injected during the AH fail to elicit action potentials.…”
Section: Morphological Analysismentioning
confidence: 99%
“…Varicosities containing numerous elongated structures resembling those found in the guinea pig caecum ( fig. 25 in Cook & Burnstock, 1976) were very occasionally seen. However, axon varicosities characterised by small granular vesicles and by heterogeneous populations of vesicles (Baumgarten et al 1970) were not found.…”
Section: Ganglion Cellsmentioning
confidence: 99%
“…The precise combinations of neurotransmitters (and neuromodulators) contained in individual neurons and their projections and central connections, termed their chemical coding, have been defined in studies of the enteric nervous system (28). Ultrastructural studies of the enteric nervous system offered the first suggestion that there were several different cotransmitters in autonomic nerves; at least nine distinguishable types of axon profiles showing different combinations of vesicle types were described in the guinea pig myenteric plexus (29).…”
Section: Cotransmissionmentioning
confidence: 99%